Laminated paper for packaging and preparation method thereof
Through spraying technology and drying and winding process of modifying corn starch citrate and alginic acid, coating paper with excellent degradability and low temperature resistance is prepared, solving the problems of poor biodegradation performance and inability to low temperature resistance in existing coating papers.
Patent Information
- Application Number
- CN202510265011.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-03-07
AI Technical Summary
The existing coating paper has poor biodegradation performance, low biodegradation rate and is not resistant to low temperatures.
Using modified corn starch citrate and alginic acid, a double-layer coating structure was formed on bamboo pulp paper through spraying technology, and coating paper with excellent degradability and low temperature resistance was prepared through drying and winding process.
The 45-day biodecomposition rate of the coating paper has been achieved to reach more than 84%, the maximum biodecomposition rate has reached more than 93%, and it has excellent fresh preservation effect and good low temperature resistance.
Smart Images

Figure SMS_14 
Figure SMS_15 
Figure SMS_16
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of laminated paper and its production technology, and in particular to laminated paper for packaging and a preparation method thereof. Background Art
[0002] Laminated paper refers to a composite material formed by coating and bonding plastic particles to the surface of paper through a casting method. Its main feature is that the characteristics of plastic particles give the paper excellent waterproof and oil-proof properties.
[0003] As people's awareness of safety and environmental protection increases, recycled or degradable products are becoming more and more popular in packaging. Therefore, it is very necessary to provide a safe, environmentally friendly and highly degradable coated paper.
[0004] In the prior art, patent application number 202011418161.4 discloses a degradable food packaging coated paper, its preparation method, and application. This technology involves mixing and dissolving a dissolving pulp with an aqueous solution of N-methylmorpholine-N-oxide, followed by washing with water to obtain a regenerated cellulose suspension. Citrate starch, glycerol, citric acid, regenerated cellulose, a defoamer, and a dispersant are added to water in proportion and stirred continuously. The mixture is heated to 80-90°C for dissolution and gelatinization for 30-60 minutes, diluted to a concentration of 5-10%, and then loaded into the hopper of a laminating machine. The mixture is sprayed onto the surface of the base paper and dried to obtain the degradable food packaging coated paper. This degradable food packaging coated paper exhibits excellent water and oil resistance, as well as physical properties. While this technology improves the water and oil resistance and physical properties of the coated paper, its low-temperature resistance is poor, making it unsuitable for packaging materials requiring freshness preservation. Patent application number 201811546090.9: A photo-oxidatively degradable polyethylene coated paper, its preparation method, and its application. This polyethylene coated paper comprises a base paper and a coating material. The coating material comprises the following components, in weight percentage: 75-85% polyethylene, 0.5-1.5% photo-oxidatively degradable masterbatch, 10-20% water-soluble glue, 0.2-1% degradation accelerator, and 1-3% nano-organic montmorillonite. The polyethylene coated paper of this invention exhibits excellent paper-plastic separation, rapid degradation, and no harmful effects on animals, plants, or soil. It also exhibits excellent mechanical properties, is easy to process, is non-toxic, environmentally friendly, and highly safe. While this technology significantly improves mechanical properties, its microbial decomposition is limited. Patent application number 202010138716.3: A fully biodegradable coated paper and its preparation method. The fully biodegradable laminated paper is composed of a composite of laminated paper and a biodegradable film. The biodegradable film is coated with a biodegradable resin. The resulting fully biodegradable laminated paper has a simple structure, consisting solely of laminated paper and a biodegradable film. Furthermore, the raw material for the biodegradable film overcomes the low heat deformation temperature of PBAT, eliminating the need for blending and modification with PLA. This significantly reduces production costs and improves efficiency. However, the products produced using this technology are not resistant to low temperatures and exhibit suboptimal mechanical properties.
[0005] In summary, the coated paper in the prior art has the following technical defects: poor biodegradability, low biodegradation rate, and low temperature resistance. Summary of the Invention
[0006] In response to the above technical problems, the present invention provides a method for preparing laminated paper for packaging, which aims to achieve the following invention objectives: having excellent degradability and low-temperature resistance, and being non-toxic and highly safe to use.
[0007] In order to achieve the above-mentioned purpose of the invention, the following technical solutions are adopted: A method for preparing laminated paper for packaging, comprising the following steps: Step 1: Preparation of modified corn starch citrate In a reactor, prepare a 0.8-1.2% by weight citric acid solution with distilled water. Heat the citric acid solution to 35-38°C and stir at 120-150 rpm. Add corn starch to the citric acid solution while stirring and allow to react for 2.5-3 hours. Then, adjust the pH of the solution in the reactor to 8.2 with sodium hydroxide, cool to 26-28°C, add octenylsuccinic anhydride and sodium alginate, and continue stirring for 30-50 minutes.
[0008] After the reaction, the mixture was allowed to stand at room temperature for 16 hours and filtered; the filtered solid was dried at 60°C for 6 to 9 hours and ground to 80 to 100 meshes to obtain modified corn starch citrate.
[0009] The amounts of citric acid, corn starch, octenyl succinic anhydride and sodium alginate used, in parts by weight, are: 20-27 parts of citric acid, 50-62 parts of corn starch, 5.5-7.5 parts of octenyl succinic anhydride and 0.8-1.2 parts of sodium alginate.
[0010] Step 2: Prepare the coating material The coating raw materials (in parts by weight) include 20-25 parts of modified corn starch citrate, 75-80 parts of alginic acid, 20-25 parts of polypropylene carbonate, 20-25 parts of polylactic acid, 1-3 parts of glycerol, 1-3 parts of polyhydroxystearic acid, and 2-2.5 parts of carboxymethyl cellulose.
[0011] Prepare laminating raw materials, place the laminating raw materials in a mixer, heat and mix them, the heating temperature is 120-128° C., and the heating time is 60-100 min to obtain the laminating material.
[0012] Step 3. Select the base paper Select a water content of 1% to 5% and a thickness of 30 ~100 Bamboo pulp paper is used as the base paper.
[0013] Step 4: Initial coating Put the coating material prepared in step 2 into the feeding hopper of the coating machine and spray it on both sides of the base paper. The coating amount on one side is 4-8g / , and obtain the primary laminated paper.
[0014] Step 5: Secondary coating The primary coated paper is introduced into the laminating machine again for secondary laminating. The laminating method is the same as the primary laminating method. The laminating amount on one side is 5-10g / , and get the coated paper.
[0015] Step 6: Drying and rolling The laminated paper obtained in step 5 is placed in a drying oven for drying at a temperature of 60 to 90° C. for 3 to 5 minutes. The dried laminated paper is allowed to stand and cool, and is rolled up to obtain a finished product.
[0016] By adopting the above technical solution, the present invention achieves the following beneficial effects: 1. The coated paper prepared by the method of the present invention is easily biodegradable, with a biodegradation rate of more than 84% in 45 days and a maximum biodegradation rate of more than 93%.
[0017] 2. The coated paper prepared by the method of the present invention has excellent preservation effect, and the oxygen permeability is less than 7cm 3 / (m 2 ·24h·0.1MPa), water vapor transmission rate is less than 8g / (m 2 ·24h).
[0018] 3. The coated paper prepared by the method of the present invention has good ester resistance and permeability, and has good low-temperature resistance.
[0019] 4. The coated paper prepared by the method of the present invention uses safe and environmentally friendly materials, and the finished product is easily degradable and suitable for market promotion and use. DETAILED DESCRIPTION
[0020] Example 1: A method for preparing laminated paper for packaging The specific steps are as follows: Step 1: Preparation of modified corn starch citrate In a reactor, prepare a 1% by weight citric acid solution with distilled water. Heat the citric acid solution to 35°C and stir at 120 rpm. Add corn starch to the citric acid solution while stirring, and allow to react for 2.5 hours. Then, adjust the pH of the solution in the reactor to 8.2 with sodium hydroxide, cool to 28°C, add octenylsuccinic anhydride and sodium alginate, and continue stirring for 50 minutes.
[0021] After the reaction, the mixture was allowed to stand at room temperature for 16 h and filtered; the filtered solid was dried at 60° C. for 9 h and ground into 80 mesh, thereby obtaining modified corn starch citrate.
[0022] The amounts of citric acid, corn starch, octenylsuccinic anhydride and sodium alginate used, in parts by weight, are: 20 parts of citric acid, 50 parts of corn starch, 5.5 parts of octenylsuccinic anhydride and 1.2 parts of sodium alginate.
[0023] Step 2: Prepare the coating material The coating raw materials, in parts by weight, have the following component ratios: 20 parts of modified corn starch citrate, 80 parts of alginic acid, 25 parts of polypropylene carbonate, 20 parts of polylactic acid, 1 part of glycerol, 3 parts of polyhydroxystearic acid, and 2 parts of carboxymethyl cellulose.
[0024] Prepare the laminating raw materials, place the laminating raw materials in a mixer, heat and mix them, the heating temperature is 128° C., and the heating time is 60 min to obtain the laminating material.
[0025] Step 3. Select the base paper The water content is 5%, the thickness is 80 Bamboo pulp paper is used as the base paper.
[0026] Step 4: Initial coating Put the coating material prepared in step 2 into the feeding hopper of the coating machine and spray it on both sides of the base paper. The coating amount on one side is 6g / , and obtain the primary laminated paper.
[0027] Step 5: Secondary coating The primary coated paper is introduced into the laminating machine again for secondary lamination. The lamination amount on one side is 8g / , and get the coated paper.
[0028] Step 6: Drying and rolling The laminated paper obtained in step 5 was placed in a drying oven for drying at a drying temperature of 75° C. for 3 min. The dried laminated paper was allowed to stand for 2 h and then rolled up to obtain a finished product.
[0029] Example 2: A method for preparing laminated paper for packaging The specific steps are as follows: Step 1: Preparation of modified corn starch citrate In a reactor, prepare a 1% by weight citric acid solution with distilled water. Heat the citric acid solution to 36°C and stir at 120 rpm. Add corn starch to the citric acid solution while stirring and allow to react for 2.5 hours. Then, adjust the pH of the solution in the reactor to 8.2 with sodium hydroxide, cool to 28°C, add octenylsuccinic anhydride and sodium alginate, and continue stirring for 30 minutes.
[0030] After the reaction, the mixture was allowed to stand at room temperature for 16 h and filtered; the filtered solid was dried at 60° C. for 9 h and ground into 100 mesh to obtain modified corn starch citrate.
[0031] The amounts of citric acid, corn starch, octenylsuccinic anhydride and sodium alginate used, in parts by weight, are: 24 parts of citric acid, 60 parts of corn starch, 7.5 parts of octenylsuccinic anhydride and 0.8 parts of sodium alginate.
[0032] Step 2: Prepare the coating material The coating raw materials, in parts by weight, have the following component ratios: 20 parts of modified corn starch citrate, 75 parts of alginic acid, 25 parts of polypropylene carbonate, 25 parts of polylactic acid, 3 parts of glycerol, 3 parts of polyhydroxystearic acid, and 2 parts of carboxymethyl cellulose.
[0033] Prepare the laminating raw materials, place the laminating raw materials in a mixer and heat and mix them at a heating temperature of 120° C. for 100 min to obtain the laminating material.
[0034] Step 3. Select the base paper The water content is 5%, the thickness is 80 Bamboo pulp paper is used as the base paper.
[0035] Step 4: Initial coating Put the coating material prepared in step 2 into the feeding hopper of the coating machine and spray it on both sides of the base paper. The coating amount on one side is 6g / , and obtain the primary laminated paper.
[0036] Step 5: Secondary coating The primary coated paper is introduced into the laminating machine again for secondary lamination. The lamination amount on one side is 8g / , and get the coated paper.
[0037] Step 6: Drying and rolling The laminated paper obtained in step 5 was placed in a drying oven for drying at a drying temperature of 75° C. for 3 min. The dried laminated paper was allowed to stand for 2 h and then rolled up to obtain a finished product.
[0038] Example 3: A method for preparing laminated paper for packaging The specific steps are as follows: Step 1: Preparation of modified corn starch citrate In a reactor, prepare a 1% by weight citric acid solution with distilled water. Heat the citric acid solution to 38°C and stir at 140 rpm. Add corn starch to the citric acid solution while stirring. Allow to react for 3 hours. Then, adjust the pH of the solution in the reactor to 8.2 with sodium hydroxide, cool to 26°C, add octenylsuccinic anhydride and sodium alginate, and continue stirring for 40 minutes.
[0039] After the reaction, the mixture was allowed to stand at room temperature for 16 h and filtered; the filtered solid was dried at 60°C for 7 h and ground into 80 mesh to obtain modified corn starch citrate.
[0040] The amounts of citric acid, corn starch, octenylsuccinic anhydride and sodium alginate used, in parts by weight, are: 27 parts of citric acid, 55 parts of corn starch, 7.5 parts of octenylsuccinic anhydride and 1 part of sodium alginate.
[0041] Step 2: Prepare the coating material The coating raw materials, in parts by weight, have the following component ratios: 25 parts of modified corn starch citrate, 78 parts of alginic acid, 24 parts of polypropylene carbonate, 20 parts of polylactic acid, 2 parts of glycerol, 1.5 parts of polyhydroxystearic acid, and 2.5 parts of carboxymethyl cellulose.
[0042] Prepare the laminating raw materials, place the laminating raw materials in a mixer and heat and mix them at a heating temperature of 122°C for 90 min to obtain the laminating material.
[0043] Step 3. Select the base paper The water content is 5%, the thickness is 80 Bamboo pulp paper is used as the base paper.
[0044] Step 4: Initial coating Put the coating material prepared in step 2 into the feeding hopper of the coating machine and spray it on both sides of the base paper. The coating amount on one side is 6g / , and obtain the primary laminated paper.
[0045] Step 5: Secondary coating The primary coated paper is introduced into the laminating machine again for secondary lamination. The lamination amount on one side is 8g / , and get the coated paper.
[0046] Step 6: Drying and rolling The laminated paper obtained in step 5 was placed in a drying oven for drying at a drying temperature of 75° C. for 3 min. The dried laminated paper was allowed to stand for 2 h and then rolled up to obtain a finished product.
[0047] Comparative Example 1 On the basis of Example 3, step 1 for preparing modified corn starch citrate was omitted, and in step 2 for preparing the coating material, the modified corn starch citrate was replaced with corn starch citrate. The specific operation was as follows: Step 1 is not performed to prepare modified corn starch citrate; Step 2: Prepare the coating material The coating raw materials are formulated in the following proportions, in parts by weight: 25 parts of corn starch citrate, 78 parts of alginic acid, 24 parts of polypropylene carbonate, 20 parts of polylactic acid, 2 parts of glycerol, 1.5 parts of polyhydroxystearic acid, and 2.5 parts of carboxymethyl cellulose.
[0048] Prepare the laminating raw materials, place the laminating raw materials in a mixer and heat and mix them at a heating temperature of 122°C for 90 min to obtain the laminating material.
[0049] Step 3: Select base paper as in Example 3.
[0050] Step 4, the initial coating is the same as in Example 3.
[0051] Step 5, secondary coating is the same as in Example 3.
[0052] Step 6, drying and rolling, is the same as in Example 3.
[0053] Comparative Example 2 On the basis of Example 3, sodium alginate was not added to the modified corn starch citrate prepared in step 1, and the other steps remained unchanged. The specific operations were as follows: Step 1: Preparation of modified corn starch citrate In a reactor, prepare a 1% by weight citric acid solution with distilled water. Heat the citric acid solution to 38°C and stir at 140 rpm. Add corn starch to the citric acid solution while stirring. Allow to react for 3 hours. Then, adjust the pH of the solution in the reactor to 8.2 with sodium hydroxide, cool to 26°C, add octenylsuccinic anhydride, and continue stirring for 40 minutes.
[0054] After the reaction, the mixture was allowed to stand at room temperature for 16 h and filtered; the filtered solid was dried at 60°C for 7 h and ground into 80 mesh to obtain modified corn starch citrate.
[0055] The amounts of the citric acid, corn starch and octenyl succinic anhydride used, in parts by weight, are: 27 parts of citric acid, 55 parts of corn starch and 7.5 parts of octenyl succinic anhydride.
[0056] Step 2: Preparation of the coating material is the same as in Example 3.
[0057] Step 3: Select base paper as in Example 3.
[0058] Step 4, the initial coating is the same as in Example 3.
[0059] Step 5, secondary coating is the same as in Example 3.
[0060] Step 6, drying and rolling, is the same as in Example 3.
[0061] Comparative Example 3 On the basis of Example 3, the alginic acid in the coating material prepared in step 2 was replaced with citric acid, and the other steps remained unchanged. The specific operations are as follows: Step 1: Preparation of modified corn starch citrate is the same as in Example 3.
[0062] Step 2: Prepare the coating material The coating raw materials, in parts by weight, have the following component ratios: 25 parts of modified corn starch citrate, 78 parts of citric acid, 24 parts of polypropylene carbonate, 20 parts of polylactic acid, 2 parts of glycerol, 1.5 parts of polyhydroxystearic acid, and 2.5 parts of carboxymethyl cellulose.
[0063] Prepare the laminating raw materials, place the laminating raw materials in a mixer and heat and mix them at a heating temperature of 122°C for 90 min to obtain the laminating material.
[0064] Step 3: Select base paper as in Example 3.
[0065] Step 4, the initial coating is the same as in Example 3.
[0066] Step 5, secondary coating is the same as in Example 3.
[0067] Step 6, drying and rolling, is the same as in Example 3.
[0068] Comparative Example 4 On the basis of Example 3, carboxymethyl cellulose is not added to the coating material in step 2, and the other steps remain unchanged. The specific operations are as follows: Step 1: Preparation of modified corn starch citrate is the same as in Example 3.
[0069] Step 2: Prepare the coating material The coating raw materials are calculated in parts by weight and the component ratios are: 25 parts of modified corn starch citrate, 78 parts of alginic acid, 24 parts of polypropylene carbonate, 20 parts of polylactic acid, 2 parts of glycerol, and 1.5 parts of polyhydroxystearic acid.
[0070] Prepare the laminating raw materials, place the laminating raw materials in a mixer and heat and mix them at a heating temperature of 122°C for 90 min to obtain the laminating material.
[0071] Step 3: Select base paper as in Example 3.
[0072] Step 4, the initial coating is the same as in Example 3.
[0073] Step 5, secondary coating is the same as in Example 3.
[0074] Step 6, drying and rolling, is the same as in Example 3.
[0075] Comparative Example 5 On the basis of Example 3, polyhydroxystearic acid is not added in the preparation of the coating material in step 2, and the other steps remain unchanged. The specific operations are as follows: Step 1: Preparation of modified corn starch citrate is the same as in Example 3.
[0076] Step 2: Prepare the coating material The coating raw materials are calculated in parts by weight and the component ratios are: 25 parts of modified corn starch citrate, 78 parts of alginic acid, 24 parts of polypropylene carbonate, 20 parts of polylactic acid, 2 parts of glycerol, and 2.5 parts of carboxymethyl cellulose.
[0077] Prepare the laminating raw materials, place the laminating raw materials in a mixer and heat and mix them at a heating temperature of 122°C for 90 min to obtain the laminating material.
[0078] Step 3: Select base paper as in Example 3.
[0079] Step 4, the initial coating is the same as in Example 3.
[0080] Step 5, secondary coating is the same as in Example 3.
[0081] Step 6, drying and rolling, is the same as in Example 3.
[0082] Example 4 Performance Test Performance test of the laminated paper for packaging prepared in Examples 1-3 and Comparative Examples 1-5: 1. Sample collection was conducted in accordance with GB / T450. Sample handling and test atmosphere conditions were conducted in accordance with GB / T10739. Laminated paper was tested for the following indicators: ester resistance and permeability, in accordance with GB / T 36392-2018, Laminated Paper and Board for Food Packaging. Burst resistance was tested in accordance with GB / T 454-2002. After storing the laminated paper at -40°C for 48 hours, its burst resistance was retested (at room temperature and pressure, after the laminated paper has returned to room temperature). Ink absorption was tested in accordance with GB / T 12911-1991.
[0083] The test results are shown in Table 1.
[0084]
[0085] As shown in Table 1, the coated paper of the present invention has excellent ester resistance and permeability, high burst resistance, and resistance to low-temperature storage. The ink absorption value is 18-20%, the printed text is clean, the printed oil film is smooth, uniform, and has high gloss, and saves ink.
[0086] 2. The oxygen permeability and water vapor permeability of the coated papers prepared in Examples 1-3 and Comparative Examples 1-5 were tested according to the method of GB / T 1038.1-2022 (differential pressure method). The test results are shown in Table 2.
[0087] Table 2
[0088] Analysis of the data in Table 2 shows that the oxygen permeability and water vapor permeability of the laminated paper of Examples 1-3 are significantly lower than those of Comparative Examples 1-5, indicating that the freshness-keeping effect of the laminated paper of Examples 1-3 is significantly better than that of Comparative Examples 1-5.
[0089] 3. The degradation performance of the coated papers prepared in Examples 1-3 and Comparative Examples 1-5 was tested according to the method of GB / T 39951-2021. The test results are shown in Table 3.
[0090] Table 3
[0091] As can be seen from Table 3, the coated paper prepared by the present invention is easily biodegradable, with a biodegradation rate of more than 84% in 45 days and a maximum biodegradation rate of more than 93%.
[0092] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
Claims
1. A laminated paper for packaging, characterized in that: The raw material components include, by weight: 20-25 parts of modified corn starch citrate, 75-80 parts of alginic acid, 20-25 parts of polypropylene carbonate, 20-25 parts of polylactic acid, 1-3 parts of glycerol, 1-3 parts of polyhydroxystearic acid, and 2-2.5 parts of carboxymethyl cellulose; The preparation method of the modified corn starch citrate ester is as follows: in a reaction kettle, citric acid is prepared into a citric acid solution with a mass percentage of 0.8-1.2% by using distilled water, and the solution is heated to 35-38° C.; stirring is started; corn starch is added to the citric acid solution while stirring, and the reaction is carried out for 2.5-3 hours; then, the pH value of the solution in the reaction kettle is adjusted to be alkaline with sodium hydroxide, the temperature is lowered to 26-28° C., octenyl succinic anhydride and sodium alginate are added, and the stirring reaction is continued for 30-50 minutes; after the reaction, the solution is allowed to stand and filtered; the filtered solid is dried and ground to 80-100 meshes.
2. The laminated paper for packaging according to claim 1, characterized in that: The dosage of the citric acid, corn starch, octenyl succinic anhydride and sodium alginate is, by weight, 20 to 27 parts of citric acid, 50 to 62 parts of corn starch, 5.5 to 7.5 parts of octenyl succinic anhydride and 0.8 to 1.2 parts of sodium alginate.
3. The method for preparing a laminated paper for packaging according to claim 1, characterized in that: The coating raw materials are placed in a mixer for heating and mixing, and then sprayed onto both sides of the base paper for primary coating to obtain primary coating paper; the primary coating paper is introduced into the coating machine again for secondary coating to obtain coating paper, which is then dried and rolled up.
4. The method for preparing a laminated paper for packaging according to claim 3, characterized in that: The base paper has a moisture content of 1% to 5% and a thickness of 30 ~100 .
5. The method for preparing a laminated paper for packaging according to claim 3, characterized in that: The first coating: the coating amount on one side is 4 to 8 g / The secondary coating: the coating amount on one side is 5-10g / .
Citation Information
Patent Citations
Oxygen and light degradable polyethylene coated film and preparation and application methods thereof
CN109577100A
Full-biodegradable coated paper and preparation method thereof
CN111187494A
A biodegradable food packaging coated paper, its preparation method and application
CN112523002B
Process for preparing edible bean dreg paper
CN103806344A
High-strength papermaking sizing agent
CN110616590A
Cited By
Antibacterial coated paper and preparation method thereof
CN121250711A
Antibacterial coated paper and method for making the same
CN121250711B